Gamifying CBT to deliver emotional health treatment to young people on smartphones - Christie, Grant I. (Internet Interv, 2019)
mHealth interventions promise the economic delivery of evidence-based mental health treatments like cognitive behavioural therapy (CBT) to populations that struggle to access health services, such as adolescents and in New Zealand, Māori and Pasifika youth. Unfortunately engagement with digital therapies is poor; modularisation and gamification have potential to increase their appeal. Gamifying CBT involves selecting suitable interventions, adapting them to a digital format while applying gamification principles. We describe the design and development of Quest - Te Whitianga, an app that encourages the user to learn CBT skills via a series of activities and games. A variety of approaches including consultation with clinicians, reference to best-practice literature, focus groups and interactive workshops with youth were used to inform the co-design process. Clinicians worked iteratively with experienced game designers to co-create a youth CBT digital intervention. The Quest modular app is set on an ocean and the user travels between islands to learn six evidence-based skills. These include a relaxation/mindfulness activity, activity planning, a gratitude journal plus problem solving and communication skills training. We describe the theoretical and design aspects of each module detailing the gamified features that aim to increase user engagement. In the near future we will be testing the app and the principles discussed in this paper via a randomised-controlled trial.